Aplikasi Ujian Online Berbasis Intranet Pada Mata Pelajaran Simulasi Digital Di SMK Yadika 4 Ciledug - Mulia Rahmayu; Catur Eko Purnomo; Budi Sudrajat (PETIR, 2019)
Yadika 4 Vocational School is a vocational secondary education institution that was established in 1996 and is located on the highway Raden Saleh No. 11 Karang Tengah. Creative school that provides three majors namely Office Administration (AP), Accounting (AK) and Computer Network Engineering (TKJ). In the learning process Yadika 4 Vocational students get subject matter materials according to their competency skills. Another problem that is when the exam is still seen is cheating, such as cheating, this causes the class to become noisy. The thing that makes the writer take this online exam case study is to prepare computer-based examinations held by the education office. Other problems, namely the values that come out of each subject will be entered manually from each class by the subject teacher concerned, sometimes the teacher feels tired to count and match the answers and the scores of each subject tested. Errors when matching cause repetition of entering data into Microsoft Excel tools that are used as learning evaluation reports to the homeroom of each class. The solution to overcome this problem is by making an online test application with questions and answers on online exam applications to be random in order to minimize fraud. In the making, it is expected that online examinations in schools can provide students with an overview of computer-based exams that have been held by the education office with advantages in terms of time correction, resources from teachers (teachers or employees). The results of this study produced an online test application that has been tested, so that users in this application can be helped as the results of observations made by the author in conducting this research. i.